Characterizing the Factors Associated with Women’s Adherence to Institute of Medicine Gestational Weight Gain Guidelines and Assessing a Possible Role for Mobile Health through the Evaluation of a Pregnancy-Specific Application SmartMoms Canada - Halili, Lyra (Université d'Ottawa / University of Ottawa, 2018)
Fetal exposure to an intrauterine environment affected by maternal obesity and excessive gestational weight gain (GWG) pose several adverse short- and long-term health risks to infants. Excessive GWG and maternal obesity are of high priority to public health across many nations. Improving maternal and child health can be achieved by encouraging women to meet Institute of Medicine (IOM) weight gain recommendations, sound clinical guidance, and other forms of support. Another means of helping women adhere to weight gain guidelines is by making use of the near ubiquitous nature of mobile technology and promoting healthy pregnancies through reliable mobile health (mHealth) applications (apps). The objective of the first study of this thesis was to examine the associations between psychosocial factors and achieving IOM-recommended weight gain during pregnancy. Cross-sectional data were collected from pregnant and postpartum women who responded to a validated questionnaire, the Electronic Maternal health survey. Multiple linear logistic regression analyses were used to determine correlates associated with meeting IOM guidelines. The objective of the second study was to conduct a preliminary exploration of women’s attitudes towards an evidence-based, mHealth app, SmartMoms Canada, as a valid source of pregnancy-related information and its ability to offer physical activity, nutrition, and lifestyle support. Focus groups were organized to assess women’s attitudes towards the app and inductive thematic content analysis was utilized to interpret focus group data. It was found that self-efficacy and perceived controllability of behaviours are important factors contributing to whether women meet IOM weight gain recommendations. Further, pregnant women are quite receptive to mHealth technology and positively viewed the future prospective of SmartMoms Canada as a means of promoting overall maternal health. Combined, these findings will contribute to our understanding of how to best improve maternal-fetal health outcomes in the near future.
Keywords: Pregnancy; Excessive Gestational Weight Gain; Institute of Medicine; Mobile Health